Larvicidal Effectiveness of Betel Leaves (Piper betle Linn.) Infusa Against Mortality Aedes agypti Larvae - ., Ardiyansyah (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2017)
Background. Indonesia was a country with the most cases of Dengue Hemorrhagic Fever in South East Asia. The appropriate countermeasures such as vector control is a other  method to reduce the incidence. Abate (temephos) was reported in any countries have resistance against Aedes aegypti. Betel Leaves (Piper betel Linn) is contains essential oil, saponin, alkaloid and tannin can be expected as larvacidal effect to Aedes aegypti. larvae.   Objective. To know larvacidal effect and optimum concentration of  Betel leaves infusa is effective for killing mosquito larvae of Aedes aegypti.   Methodology. This research is experimental research with Post Test Only Control Group Design method. Aedes aegypti larvae used larvae which have developed into instar III/IV, divided into 7 groups, positive control groups (abate 10 mg/100 mL), negative control groups (aquadest), betel leaves infusa groups, 4 mL/100 mL, 5 mL/100 mL, 6 mL/100 mL, 7 mL/100 mL and 8 mL/100 mL. The each groups contains 10 larvae and  it’s repeated 4 times Parameters measured were the number of dead larvae in 24 hours. Data processed with One Way Anova test by 21th SPSS and continued with Post Hoc Least Significant Difference (LSD) test.   Result. Percentage of larvae mortality in 4 mL/100 mL infusa concentration is is 72,5%; 5 mL/100 mL is 80%; 6 mL/100 mL is 82,5%; 7 mL/100 mL is 90 % and 8 mL/100mL is 92,5% with P value is 0,022.   Conclusion. Betel leaves (Piper betle Linn) infusa have larvacidal effect against larvae of Aedes aegypti mosquitos and optimum concentration is at 7 mL/100 – 8 mL/100 mL.    Keywords: Aedes aegypti, betel leaves, mortality